Facilitators and barriers influencing the readiness to receive dental implants in a geriatric institutionalised population—A randomized non‐invasive interventional study. (28th March 2017) - Merz, Miriam A.; Terheyden, Hendrik; Huber, Christian G.; Seixas, Azizi A.; Schoetzau, Andreas; Schneeberger, Andres R.
Abstract : Objective: Although elderly people have many serious dental issues and are in need of prosthesis, few opt for dental implants. The aim of this study was to investigate barriers that prevent elderly people from receiving dental implants. Specifically, we examined (i) whether the message was delivered before or after the interview had an impact, and (ii) whether it did matter who delivered the message. Materials and Methods: Sixty‐six residents from seven residential homes in the Canton of Grisons, Switzerland were included. The sample was randomized to a treatment group that received comprehensive education about dental implants before the interview and a control group that received education after completing the questionnaire. Results: The sample consisted of 54 women (81.8%) and 12 males (18.2%) with an average age of 86.2 years. Education before the interview did not show any impact on the attitude towards dental implants. Main reasons for a negative attitude towards implants were old age and high costs. Participants who received information about implants from their relatives and their own dentist and not from the study dentist were significantly more willing to receive implants. Conclusion: Providing an adequate education about benefits and risks of receiving dental implants does not change the attitude towards dental implants. The source of information/messenger does influence attitudes towards implants. If the person delivering the education and information is a relative or a known medical person, the person's attitude is more likely to change as compared to people receiving the information from an unrelated person.